Nephrogenic Diabetes Insipidus Secondary to Obstructive Uropathy – An Unusual Presentation- A Case Report - Rahman, Md Habibur; Rahman, MD Azizur; Huque, Syed Saimul (Journal of Pediatric Nephrology, 2016)
Diabetes insipidus is a clinical condition, characterized by polyuria and polydipsia, that results from either insufficient production or end organ resistance to antidiuretic hormone (ADH). Diabetes insipidus is of two types: central diabetes insipidus (CDI) and nephrogenic diabetes insipidus (NDI).Children with diabetes insipidus may present with polyuria, polydipsia, frequent dehydration, constipation, and failure to thrive. Acquired NDI may results from various drugs and conditions but NDI due to obstructive uropathy is very rare. There are very few case reports of NDI due to obstructive uropathy. We report a 2-year-old child who presented with diabetes insipidus as a consequence of obstructive uropathy. Keywords: Nephrogenic diabetes insipidus; Obstructive Uropathy; Child.